Lithium‐Doped Silica‐Rich MIL‐101(Cr) for Enhanced Hydrogen Uptake. Issue 20 (11th September 2019) - Panchariya, Dharmendra K.; Kumar, E. Anil; Singh, Sanjay K.
Abstract: Metal‐organic frameworks (MOFs) show promising characteristics for hydrogen storage application. In this direction, modification of under‐utilized large pore cavities of MOFs has been extensively explored as a promising strategy to further enhance the hydrogen storage properties of MOFs. Here, we described a simple methodology to enhance the hydrogen uptake properties of RHA incorporated MIL‐101 (RHA‐MIL‐101, where RHA is rice husk ash—a waste material) by controlled doping of Li + ions. The hydrogen gas uptake of Li‐doped RHA‐MIL‐101 is significantly higher (up to 72 %) compared to the undoped RHA‐MIL‐101, where the content of Li + ions doping greatly influenced the hydrogen uptake properties. We attributed the observed enhancement in the hydrogen gas uptake of Li‐doped RHA‐MIL‐101 to the favorable Li + ion‐to‐H2 interactions and the cooperative effect of silanol bonds of silica‐rich rice‐husk ash incorporated in MIL‐101. Abstract : Significantly enhanced hydrogen uptake is achieved for silica‐rich rice‐husk ash (RHA) incorporated MIL‐101 by controlled doping of Li + ions. Studies evidenced that the content of Li + ion doping greatly influenced the hydrogen uptake properties, which is attributed to the favorable Li + ion‐to‐H2 interactions and the effect of silanol bonds of silica‐rich RHA incorporated in MIL‐101.